Adapt LLC - LLC, Adapt
Doing Development Differently… Adapt LLC provides expertise to interna tional development practitioners seeking to improve the impacts of the ir investments through a more in-depth understanding of the political and economic risks and opportunities associated with programming in co mplex environments. The Adapt team enhances the design and implementat ion of international development assistance strategies, programs, and projects around the world.